Microplastics in urban soils from different land use activities of Cyberjaya (Malaysia): exploring occurrence, relationships, sources and pollution level - Praveena, Sarva Mangala; Nik Mohd Zaidi, Nik Munirah; Nafisyah, Ayu Lana; Lingaraju, H.G. (John Wiley and Sons, 2024)
As human activities continue to increase, the production and utilisation of plastics have become pervasive, leading to a surplus of plastic waste in the environment. This has turned the terrestrial ecosystem, encompassing soil, into a significant receptacle for the growing accumulation and discharge of plastic waste. Thus, the objective of this study is to investigate the occurrence, relationships, sources and pollution levels of microplastics in urban soils from different land use activities in Cyberjaya, Malaysia. Surface soil samples were collected from land uses (i.e., vacant areas, residential areas, commercial areas, construction areas and roadways). These surface soil samples were analysed for microplastic occurrence using density separation, microscopy and spectroscopy methods. The microplastics particles were analysed for size, colour and shape. Selected microplastics particles were also analysed for its plastics polymers using Fourier-Transform Infrared Spectroscopy. Microplastics occurrence ranged from 0.3 to 1.5 particle/kg, with the highest average occurrence in the construction area (0.69 particle/kg) and lowest in the vacant area (0.33 particle/kg). Microplastics particle size was shortest in commercial areas (586.08 μm) and longest in vacant areas (793.78 μm). There were no similarities between microplastics occurrence and particle size across these different land use activities, suggesting that the microplastics occurrence in urban soils depends on external disturbances during each land use activity. Significant correlation between microplastic particle size and temperature (r 2 = 0.517) showed that each land use activity is influenced by external disturbances. The I geo values showed that the microplastics pollution level in urban soils is classified as uncontaminated to moderately contaminated. Microplastic particles in urban soils were found in various shapes (i.e., fragments, films and fibres) and colours (i.e., transparent, grey, blue, red, green, purple, black, white and yellow) along with plastic polymer types (i.e., ABS, PET, PP, PE and PS) due to traffic volume, tyre wear, mismanaged plastic waste and degradation rate. This study highlights the need for pollution management and waste disposal to avoid urban environmental problems and adverse health effects.